4D printing of Magnetic Shape Memory Alloys - Milleret, Anastassia (Cranfield University, 2022)
Magnetic shape memory alloys (MSMA) are ferromagnetic materials exhibiting a plastic reversible transformation when subjected to a magnetic field. This transformation occurs within few milliseconds, making them good candidates for ultra-fast actuators. Previous studies have reported an increase of the shape memory effect in bamboo-like Ni-Mn-Ga structures. Thus, 3D Printing, using Laser Powder Bed Fusion (l-PBF), is a potential manufacturing approach to fabricate near-net-shape textured MSMAs structures. This study investigates the influence of l-PBF process parameters (laser power, scan speed, hatch spacing and scanning strategy) on the relative density and the microstructure of bulk and lattice specimens made from a gas atomised Ni-Mn-Ga powder doped with excess Mn. The as-built bulk samples showed a high relative density, up to 98% with a homogenous 14M structure and a ferromagnetic behaviour. The residual porosity in the bulk material is mainly due to gas voids, lack of fusion and cracking. Fabrication of lattice structures at a low laser power (70W) and scan speed (450 mm/s) resulted in a significant decrease in cracking. The effect of process parameters on the strut’s geometry was also investigated, in addition the influence of the lattice geometries on the magnetic properties. Microstructural analysis revealed a layered microstructure with a stripe-like surface relief that originated from the presence of martensitic twins within the sample. Further work will focus on developing a new design to enhance the magnetic properties.
Keywords: DSDS21'; 'DSDS21 3MT'; 'Magnetic Shape Memory Alloy'; '4D printing'; 'Additive manufacturing'; 'Additive Manufacturing'